Low-cost platform for real time data acquisition and fractional control with application to a DC motor - Berkani, Hemza Abdel Fettah; Keziz, Bouziane; Lashab, Mohamed; Djouambi, Abdelbaki; Kerouche, Abdelfetah (Institute of Advanced Engineering and Science, 2023)
This paper presents a low-cost experimental platform for real time data acquisition, identification and fractional order control of some low dynamic systems using Arduino-Simulink interface. As a demonstrative example, a DC motor is considered and modeled as a first order plus time delay plant (FOPTD) using data acquisition-based Arduino setup. Then, simple analytical rules are used to design a robust fractional order controller (FOC) which required a high-performance computing. Several validation tests have been carried out using Arduino–Simulink interface. The comparison between the theoretical simulation and the experimental tests confirms that the proposed interface can be used to support research and teaching of feedback control systems using experimental tests and low-cost laboratory kit.